2023
DOI: 10.1038/s41598-023-29018-9
|View full text |Cite
|
Sign up to set email alerts
|

A multinational empirical study of perceived cyber barriers to automated vehicles deployment

Abstract: The digital transformation of Automated Vehicles (AVs) has raised concerns in the cyber realm among prospective AV consumers. However, there is a dearth of empirical research on how cyber obstacles may impact the operation of AVs. To address this knowledge gap, this study examines the six critical cyber impediments (data privacy, AV connectivity, ITS infrastructure, lack of cybersecurity regulations, AV cybersecurity understanding, and AV cyber-insurance) that influence the deployment of AVs. The impact of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…(4) Concerned authorities can appoint an independent and certified tester to test maturity standards of AVs and AV producers and set some baseline standards to be maintained in order to achieve trust in AVs and increase their performance [92]. (5) As elderly people are reluctant to drive AVs, appropriate actions should be taken to change their perceptions and boost overall acceptance by increasing trust in AVs and foregrounding features and benefits of AVs [83,94,95]. ( 6) Transportation engineers and designers should simplify the design and positioning of SAVs by providing clear video instructions, internet cafes, conference rooms, and social networking places to engage all people and make their journey fun and enjoyable [90,94].…”
Section: Policy Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Concerned authorities can appoint an independent and certified tester to test maturity standards of AVs and AV producers and set some baseline standards to be maintained in order to achieve trust in AVs and increase their performance [92]. (5) As elderly people are reluctant to drive AVs, appropriate actions should be taken to change their perceptions and boost overall acceptance by increasing trust in AVs and foregrounding features and benefits of AVs [83,94,95]. ( 6) Transportation engineers and designers should simplify the design and positioning of SAVs by providing clear video instructions, internet cafes, conference rooms, and social networking places to engage all people and make their journey fun and enjoyable [90,94].…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…( 7) Auto manufacturers and interested stakeholders should invest more and strengthen research and development of this evolving technology in order to constantly improve the reliability of the technology and increase people's trust in order to enhance public acceptance of AVs [90]. (8) Practitioners should establish a set of comprehensive mitigation strategies, such as limiting personal data acquisition, anonymizing users' identities before sharing data, instituting strict regulatory frameworks in cyberspace to safeguard consumer data from cyber-attacks, and alleviate cyber worries [95]. This can increase the acceptance and use of AVs by all cohorts of the society.…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…The results revealed that males with higher travel needs, and affordability are likely to accept AVs because of higher familiarity and more experience and experience in riding AVs is the most influential factor. Similarly, through a survey of participants from four developed countries regarding perceived cyber barriers to automated vehicles deployment, Khan et al [47] identified data privacy as one of the cyber impediments that influence the deployment of AVs. Further, the study demonstrated differences in perceptions of cyber barriers and AVs deployments based on gender, age, income, and geographic location, highlighting the need to explore the socio-demographic differences for adoption and deployment of AVs.…”
Section: Literature Reviewmentioning
confidence: 99%